PERBANDINGAN KINERJA REKSA DANA SYARIAH DENGAN REKSA DANA KONVENSIONAL - Rica Rahim Lubis; Dewi Tamora Siregar; M. Ziqhri Anhar Nasution (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the performance comparison between Islamic mutual funds and conventional mutual funds in Indonesia. The research employs a descriptive qualitative method using secondary data from performance reports, regulations, and academic literature. The findings indicate that Islamic mutual funds demonstrate better stability and relatively controlled risk due to restrictions based on Sharia principles in selecting investment instruments. In contrast, conventional mutual funds offer broader flexibility and higher return potential but with greater risk exposure. Therefore, the choice between the two types of mutual funds is strongly influenced by investors’ risk profiles, investment objectives, and personal values.